ANALISIS TERHADAP TINGGINYA ANGKA PUTUS SEKOLAH SISWA SMP TERBUKA - T Effendy Suryana (IKIP Siliwangi Bandung, 2012)
The research was to get a description about the factors that caused SMP Terbuka drop out rates highly at SMP Terbuka Pacet and the cope efforts must be done by someone that concern to it. The focus are : (1) how is the student’s motivation and a social economic conditions that cause drop out rates highly? (2) how is the human resources, facilities, and fund that cause drop out rates highly? (3) how is the leadership being done by head teacher that cause drop out rates highly? (4) how is the teaching learning process to cause drop out rates highly? (5) how is the societies and compulsory basic education coordination team support that cause drop out rates highly? and (6) how are alternative efforts to reduce the drop out rates that must be done by a head teacher, managers, teachers, parents, the societies and compulsory basic education coordination team at SMP Terbuka Pacet? As a conceptual reference, I wrote the administration theory, the leadership theory, and the open distance learning theory. The research was held at SMP Terbuka Pacet, Pacet Sub district, Bandung regency, with the main school is at SMP Negeri 1 Pacet and the independent learning places (TKB) are Padaulun, Ciherang, and Cisaat. This is a qualitative descriptive approachment, to describe a current fact at this time. The data and information were collected by interview, observation, and documentation. The results showed that main factor drop outs is economic factor. And less facilities in the independent learning places that cause students was bored in their learning activities. Based on the result above, the related ones had better find a fund for scholarship, in order to make a teaching learning activities at SMP Negeri 1 Pacet as main school, and to empower all facilities in teaching learning process.